2015
DOI: 10.1021/acs.est.5b01896
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling of Packing-Peanuts into Carbon Microsheet Anodes for Lithium-Ion Batteries

Abstract: Porous carbon microsheet anodes with Li-ion storage capacity exceeding the theoretical limit are for the first time derived from waste packing-peanuts. Crystallinity, surface area, and porosity of these 1 μm thick carbon sheets were tuned by varying the processing temperature. Anodes composed of the carbon sheets outperformed the electrochemical properties of commercial graphitic anode in Li-ion batteries. At a current density of 0.1 C, carbon microsheet anodes exhibited a specific capacity of 420 mAh/g, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…[33] Hence, we see the composite provides much robust and high specific capacities compared to commercial graphite. This is much higher when compared to that reported for commercial graphite.…”
Section: Electrochemical Performance Of the Tailored Composite Gcsi Amentioning
confidence: 82%
See 1 more Smart Citation
“…[33] Hence, we see the composite provides much robust and high specific capacities compared to commercial graphite. This is much higher when compared to that reported for commercial graphite.…”
Section: Electrochemical Performance Of the Tailored Composite Gcsi Amentioning
confidence: 82%
“…Etacheri et al reported capacities of 330, 250, and 70 mAh g −1 at current densities of C/10, C/5, and 1C for commercial graphite material. [33] Adv. Energy Mater.…”
Section: Electrochemical Performance Of the Tailored Composite Gcsi Amentioning
confidence: 99%
“…As shown in Figure a, b, SEM images of the sample reveal the presence of sheet‐like morphology with a thickness of ≈1 μm and width distribution of 5–50 μm. The carbon sheets originated from the thin walls of the expanded starch packing peanuts . A transmission electron microscopy (TEM) image of the sheets in Figure c indicates the lack of long‐range ordering of the carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of carbon sheets by controlled pyrolysis of starch‐based packing peanuts was detailed in our previous study . Briefly, commercially available starch based packing peanuts were manually compressed inside an alumina crucible and pyrolyzed at 600 °C for 3 h inside a tube furnace with continuous argon flow.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] Numerous methods have been developed to create more porosityi nc arbon electrodes because ah igher surfacea rea enables easier transporto fe lectrolytic ions by shortening ion diffusion distances. For example, porosity can be generated by using sacrificialh ard-templates (e.g.,z eolites, mesoporouss ilicaa nd colloidal crystals) [6,7] and soft templates (e.g.,block copolymers), [8,9] as well as the carbonization and activation of natural waste materials [10][11][12] and high temperature chlorination of crystalline carbides. [13,14] In recent years, metalorganic frameworks (MOFs) have been used as sacrificial templates to generate nanoporous carbonm aterials.…”
Section: Introductionmentioning
confidence: 99%